The digital agriculture project has transformed the use of data to promote climate smart agriculture in Latin America. - Jimenez, Daniel (2022)
The Digital Agriculture project has transformed the use of data to support promoting climate smart agriculture and increasing yields in eight Latin American countries. It has promoted new open-source data analysis tools, built capacities to use the new technologies and assisted in the creation and application of new data sets to support decision- making. This has begun transforming institutional support systems to make better use of the new technologies, increased demand for training, and improved decision support.